Clio and the poets : Augustan poetry and the traditions of ancient historiography - Levene, D. S.; Nelis, Damien. (Mnemosyne, Supplements, 2002)
The Augustan age was one in which writers were constantly reworking the Roman past, and which was marked by a profound engagement of poets with the historians and historical techniques which were the main vehicle for the transmission of the image of the past to their day. In this book seventeen leading scholars from Europe and America examine the fascinating interaction between such apparently diverse genres: how the Augustan poets drew on - or reacted against - the historians' presentation of the world, and how, conversely, historians picked up and transformed poetic themes for their own ends. With essays on poems from Horace's Odes to Ovid's Metamorphoses , on authors from Virgil to Valerius Maximus, it forms the most important topic so central to such a particulary relevant period of literary history.